Extended discrete‐time transfer matrix approach to modeling and decentralized control of lattice‐based structures. Issue 10 (1st February 2016) - Cramer, Nick; Swei, Sean Shan‐Min; Cheung, Kenneth C.; Teodorescu, Mircea
Summary: This paper presents the modeling and control of an aircraft wing structure constructed by lattice‐based cellular materials/components. A novel model reduction process is proposed that utilizes the extended discrete‐time transfer matrix method (E‐DT‐TMM). Through recursive application of the E‐DT‐TMM, an effective reduced‐order model can be obtained in which a decentralized discrete‐time linear quadratic regulator (LQR) controller can be designed. To demonstrate the efficiency of the proposed concept, a prototype wing structure is studied. The analysis and simulation results show that the performance of the proposed E‐DT‐TMM based decentralized LQR controller is comparable with that of the full‐state continuous LQR controller. Copyright © 2016 John Wiley & Sons, Ltd.